WAYS TO IMPROVE THE QUALITY OF ADMINISTRATIVE SERVICES IN UKRAINE - Grabar N.S. (Pressing Problems of Public Administration, 2015)
The notion and types of administrative services. With the results of the survey identified the main problems of administrative services in Ukraine. On the basis of summarizing the European experience suggests concrete ways to improve the quality of administrative services, which, in particular, include the introduction of modern methods of assessing the quality of service, active involvement in the process of public approval clear classification of services, the development of electronic services, etc.